Integrating Peace and Security Education into the Civic Education Curriculum: Implications for Social Stability in Zamfara State, Nigeria - Sule Muhammad; Abdullahi Abdulhamid (Demagogi: Journal of Social Sciences, Economics and Education, 2026)
The persistent insecurity and violent conflicts in Zamfara State, Nigeria, have highlighted the critical need for educational strategies that foster peace, security awareness, and social stability. This study examined the integration of peace and security education into the Civic Education curriculum in secondary schools and its implications for students’ attitudes and broader societal stability. Guided by the objectives of assessing the extent of integration, evaluating its influence on students’ attitudes toward peaceful coexistence and community security, and identifying challenges impeding effective implementation, the study employed a descriptive survey research design. The population included senior secondary school students (SS I–SS III), Civic Education teachers, and school principals, with a sample of 384 respondents selected through multi-stage and purposive sampling techniques. Data were collected via a structured questionnaire, validated by experts and piloted for reliability (r = 0.89). Inferential statistics, including one-sample t-test, independent samples t-test, and multiple regression analysis, were used to test the hypotheses at a 0.05 level of significance. Findings revealed that peace and security education is significantly integrated into the Civic Education curriculum (t = 7.21, p < .05) and positively influences students’ attitudes toward peaceful coexistence and community security (t = 6.27, p < .05). However, effective integration is constrained by challenges including inadequate teacher training (β = 0.312, p < .05), curriculum overload (β = 0.268, p < .05), lack of instructional materials (β = 0.241, p < .05), and security challenges in schools (β = 0.289, p < .05). These barriers limit students’ exposure to practical peacebuilding skills, conflict resolution competencies, and values necessary for social stability. The study concludes that while Civic Education provides a vital platform for promoting peace and security awareness, its transformative potential requires supportive teacher preparation, adequate learning resources, and secure learning environments. Policymakers and educational authorities are encouraged to strengthen teacher capacity, streamline the curriculum, provide instructional resources, and institutionalize peace and security education to enhance students’ civic competencies and contribute to sustainable social stability in conflict-affected regions such as Zamfara State.